Network Expansion to Mitigate Market Power: How Increased Integration Fosters Welfare - Alexander Zerrahn; Daniel Huppmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Lack of transmission capacity hampers the efficient integration of the European electricity market, and thereby precludes reaping the full benefits of competition. We investigate to what extent the expansion of the transmission grid promotes competition, efficiency, and welfare. This work proposes a three-stage model for grid investment: a benevolent planner decides on network upgrades; she considers the welfare benefits of investment through a reduction of market power exertion by strategic generators. These firms anticipate their impact on the Independent System Operator and are able to exert market power, in particular when lines are congested. We illustrate the model on a simple three-node network. Results indicate that network expansion indeed provides a suitable way of enhancing welfare due to a reduction of market power potential.
Keywords: L13; L51; C61; 330